Implementation of the Project Based Learning Model in Class V Elementary School Science Content - Hayani, Fahira Hasmi (Program Magister Teknologi Pendidikan Universitas Jambi, 2017)
This research was conducted with the aim of describing the implementation of the project based learning model in class V science content at State Elementary School 47/IV, Jambi City. This research uses a qualitative approach with a phenomenological type of research. The data sources in this research were class teachers and class V students at State Elementary School 47/IV, Jambi City. Data collection techniques in this research used interviews and documentation. The data obtained was analyzed in stages, first data reduction, second data presentation, third drawing conclusions and data verification. The results of this research show that the implementation of the project based learning model on science content at State Elementary School 47/IV Jambi City has three stages in implementation, namely: (1) preparation stage. (2) implementation stage. (3) follow-up stage. From the research results, it can be concluded that in implementing the project based learning model in class V science content at State Elementary School 47/IV Jambi City, this is a learning model applied by class V teachers at State Elementary School 47/IV Jambi City, thus creating interesting learning in learning.